2010
DOI: 10.21168/rbrh.v15n4.p57-67
|View full text |Cite
|
Sign up to set email alerts
|

Cálculo do Volume e Análise da Deposição de Sedimentos do Reservatório de Três Irmãos

Abstract: var as áreas onde houve depósito e compactação de sedimentos. As erosões se concentram no leito do rio e nas margens e atingiram uma escavação de aproximadamente 12 m. Os maiores depósitos de sedimentos se concentram no início do barramento e nas entradas dos afluentes e chegam a alcançar cotas em torno de 18 m acima do que era encontrado em 1972.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
5
0
2
Order By: Relevance
“…Albertin et al (2010) found a 14% reduction of reservoir capacity in 36 years. According to this author, from the moment that the accumulated sediments meet the threshold of the water intake, there are no more conditions for the proper operation of the reservoir, meaning that this is the end of its useful life.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Albertin et al (2010) found a 14% reduction of reservoir capacity in 36 years. According to this author, from the moment that the accumulated sediments meet the threshold of the water intake, there are no more conditions for the proper operation of the reservoir, meaning that this is the end of its useful life.…”
Section: Resultsmentioning
confidence: 98%
“…Due to the reduction of water flow and the enlargement of the cross section, reservoirs are eventually subjected to conditions that favor the sedimentation of solid materials carried by the watercourse or arising by runoff from the basin (ALBERTIN et al, 2010). The lack of vegetation in the basin intensifies the silting process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, coordinate transformation is not a common automatic feature for Geographic Information Systems (GIS), requiring some programming efforts that may not always be feasible. Hence, although sophisticated geostatisical techniques have been developed for interpolating bathymetric data (Legleiter; Kyriakidis, 2008;Merwade;Cook;Coonrod, 2008;Merwade, 2009), such techniques require a high level of user experience, and some users still rely on mechanical spatial prediction methods (Albertin et al, 2010;Miranda;Scarpinela;Mauad, 2013). Such methods, although simple and flexible, can be considered subjective and empirical, and provide no intrinsic estimation of the model error (Hengl, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, auxiliary maps with spatially exhaustive information are used to improve the predictions based on point observations of the target variable Rossiter, 2007). Hybrid kriging methods have been widely used in several environmental sciences, such as topographic modeling (Hengl et al, 2008), soil science (Odeh;McBratney;Chittleborough, 2006;Zhu;Lin;2010;Watt;Palmer, 2012;Qi-Yong et al, 2014), meteorology (Joyner et al, 2015) and marine sedimentology (Jerosch, 2013).…”
Section: Introductionmentioning
confidence: 99%